2007
DOI: 10.1194/jlr.m700369-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Whole body distribution of deuterated linoleic and α-linolenic acids and their metabolites in the rat

Abstract: Little is known about the uptake or metabolism of essential fatty acids (EFAs) in various mammalian organs. Thus, the distribution of deuterated a-linolenic acid (18:3n-3) and linoleic acid (18:2n-6) and their metabolites was studied using a stable isotope tracer technique. Rats were orally administered a single dose of a mixture (20 mg each) of ethyl D5-18:3n-3 and D5-18:2n-6, and 25 tissues per animal were analyzed for D5-labeled PUFAs at 4,8,24, 96, 168, 240, 360, and 600 h after dosing. Plasma, stomach, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 51 publications
(41 reference statements)
6
49
0
Order By: Relevance
“…Essential FAs are transported to the BBB either as FFAs bound to albumin or carried with lipoproteins in esterified forms (i.e., PLs and triglycerides) that enter the endothelial cells through the luminal side and are liberated by lipoprotein lipases (65)(66)(67)(68)(69). It is suggested that a number of mechanisms on the abluminal side, such as a flip-flop mechanism and transporters that are specific for essential FA, particularly DHA, ultimately facilitate their entry into the brain (67,70).…”
Section: Discussionmentioning
confidence: 99%
“…Essential FAs are transported to the BBB either as FFAs bound to albumin or carried with lipoproteins in esterified forms (i.e., PLs and triglycerides) that enter the endothelial cells through the luminal side and are liberated by lipoprotein lipases (65)(66)(67)(68)(69). It is suggested that a number of mechanisms on the abluminal side, such as a flip-flop mechanism and transporters that are specific for essential FA, particularly DHA, ultimately facilitate their entry into the brain (67,70).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, administration of LA results in a short-lived enrichment of LA in brain tissue along with a long-term accumulation of AA [13]. Dietary DHA has been reported to result in DHA enrichment of neuronal plasma membranes [14], although no association between dietary DHA and brain DHA has also been reported in aged animals [15].…”
Section: Dietary Pufasmentioning
confidence: 96%
“…Since deuterated compounds have been shown to exhibit comparable transport and uptake as their non-deuterated counterparts 27,28 this technique has great potential as a suitable 'label' for studying transport kinetics 29,30 . We applied deuterium labeling to the widely used herbicide glyphosate.…”
Section: Agrochemical Imagingmentioning
confidence: 99%